Weak nationalisms : affect and nonfiction in postwar America - Dowland, Douglas (University of Nebraska Press, 2019)
"Weak Nationalisms employs affect theory as well as traditional close reading techniques to explore the ways a range of writers negotiate nationalistic feeling that embraces core tenets of American liberalism while resisting and questioning the hierarchies that are often associated with nationalism"--